Electromagnetic Compatibility of Implantable Biomaterials for Reconstructive and Restorative Surgery of Facial Bones - О. П. Яненко; С. М. Перегудов; К. Л. Шевченко; В. О. Маланчук; В. С. Швидченко; О. Д. Головчанська (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ, 2023)
The critically important part for reconstructive and restorative surgical interventions in facial bones results is the interface of implant-tissue surfaces. The importance of taking into account the processes occurring at the border of the distribution of the implant and living tissue is due to many factors. Among them are well-known ones, such as biological compatibility, consistency of physicochemical parameters, etc. But, at the same time, the issues of electromagnetic interaction between implant materials and biological tissues remain unresolved. So, it's actual to investigate the interaction of implanted materials and tissues they are in contact. The authors considered the sources of formation of low-intensity microwave signals generated by the implant and living tissue. In this article, the authors demonstrate that microwave electromagnetic radiation is an important indicator and a new criterion for the physical compatibility of dielectric implantation biomaterials. It is proposed to use the term ``electromagnetic compatibility'' for the possibility of evaluating implant materials. This makes it possible to quantify the materials that come into contact with the human body during implantation. It should be noted that it is extremely difficult to measure the microwave radiation of the implant and biological tissue with existing technical means. This is due to the extremely low power of the emitted signals. The authors created a radiometric system with a sensitivity of 10-14 W. Using a highly sensitive radiometric system, a study of the radiation capacity of a number of implantable biomaterials was conducted. The possibility of forming positive and negative flows of microwave radiation, which can occur between adjacent tissues and implants, is shown. Violations of electromagnetic compatibility and, accordingly, the energy state of the surrounding biotissues, can qualitatively and quantitatively affect the reparative processes in the area of interventions, prolong the recovery period of adjacent tissues. So, it must be taken into account when choosing dielectric implant biomaterials.